(3TQM NdGUI GdMSGHs - (3GdHZOGOj, GdcGXej, GdLhGO GdHZOGOj, LhGO Hf SYO Hf LhGO, J (B1065(3g`s ((3CHh GdMSf Hf gGOj GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg GdhGMO (B.. (3deG cGf Yde GdMSGHeeG GTJgQ Ydh bQjfJg YfO Chdj GdCdHGH hGeJGR ef Hjf GdYdhe HVjb GdeSdc hGdeONd hHUYhHI GdehQO hGdefgd (B...(3aCMHHJ Cf CTQMg TQMG jaJM CZdGb CHhGHg (B...s
(3BNQgG (B:s
.. (3aj gPg GdQSGdI GdhLjRI Hd GdLhgQI GdYRjRI ef faGFS YQGFS bhGfjf GdMSGH eGde jMJed Edi GdGf aj QSGdI hdG cJGH aGYQa bOQgG hdG JQNU egQgG (B.. (3GfJgi cdGe GdTGQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\ 142s
(3gOjI GdYGQajf (B1\258s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdQjGVjGJs